CHANGING THE METHOD OF CALCULATION AND DEFAULT INTEREST RATE (Ekonomski signali: poslovni magazin, 2013)
The subject of analysis is new solutions enacted by the Law on default interest, and they refer to the method of calculating and to the rate of default interest. Their comparison with the solutions provided by the previous Law on the level of the default interest rate was performed, and their similarities and differences are pointed out, and the comparative terms that govern this matter are shown, while the central part of the paper focuses on the impact of changes in the method of calculating and default interest rate on the position of debtors of financial obligations. New legal solution is taken from the European Union Law and it is distinctive for the stable economy in which the reference rate fluctuations are not large. In terms of development of our economy, rapidly increase of reference rate may worsen the position of debtors of financial obligations, so that the prescribed level of the default interest rate is unacceptable and must be reduced or restricted.